Fundamentals of multilevel mesomechanics of nanostructural transitions in erythrocyte membranes and their destructions in interaction with stress hormones; Physical mesomechanics; Vol. 14, iss. 3-4, May-Aug. - Panin L. E.; Mokrushnikov P. V.; Kunitsyn V. G.; Panin V. E. Viktor Evgenyevich; Zaitsev B. N. (2011, 2011)
Stress hormones (cortisol, adrenaline, noradrenaline) are capable for nonspecific binding with erythrocyte membranes thus initiating structural-phase transitions in them. The binding constants for cortisol, adrenaline and noradrenaline are respectively 1.23·106, 6.3·106 and 1.7·106 M−1. The amount of bound hormones varies in the range 10∼10-10∼n mole/mg of protein. The binding involves hydrogen bonds, hydrophobic bonds and electrostatic bonds. Active groups of hormones (amino-, imino-, methylamine-, keto- and hydroxy-groups) interact simultaneously with CO- and NH-groups of both proteins and phospholipids. These processes underlie structural-phase transitions in an erythrocyte membrane in its interaction with stress hormones. The structural-phase transitions result in complex protein-lipid domains of increasing structural order in the membrane. At the same time, water dipoles are displaced from the domains to adjacent regions and promote membrane loosening. The membrane microviscosity thus greatly increases in the regions of both protein-lipid interactions and lipid-lipid interactions. The increase in erythrocyte membrane viscosity hampers the motion of erythrocytes through capillaries, and as a certain critical threshold is approached, this contributes to the development of tissue hypoxia. The mesomechanics of structural-phase transitions and destruction in external fields of biological membranes and nanostructured solids are qualitatively alike